Valley controlled Andreev reflection and valley-switch effect in graphene-based superconducting hybrid structures. (27th August 2019) - Niu, Zhi Ping
Abstract: The presence of the valley degree of freedom in two-dimensional materials leads to the valleytronics, in which information is encoded by the valley quantum number of the electron. For graphene-based superconducting hybrid structures, with the incoming electron and the Andreev reflected hole belonging to two opposite valleys, the Andreev reflection (AR) can be controlled by the valley degree of freedom. Here, we investigate theoretically the AR in graphene-based normal/supercondcutor junctions. Due to the interplay of the staggered potentials and the off-resonant circularly polarized light, the conductances demonstrate rich features. In particular, when the Fermi level of the normal lead is smaller than the superconducting gap, the retro AR and specular AR are well separated in energy, so we can easily distinguish them by studying the conductance spectra. More importantly, for normal/supercondcutor/normal junctions, the local AR is forbidden due to the vanishing density of states in one valley, and one may observe a valley-switch effect between perfect elastic cotunneling and perfect crossed AR, by reversing the handedness of the circularly polarized light.